2021
DOI: 10.1111/1758-2229.13010
|View full text |Cite
|
Sign up to set email alerts
|

Scaling down the microbial loop: data‐driven modelling of growth interactions in a diatom–bacterium co‐culture

Abstract: An intricate set of interactions characterizes marine ecosystems. One of the most important is represented by the microbial loop, which includes the exchange of dissolved organic matter (DOM) from phototrophic organisms to heterotrophic bacteria. Here, it can be used as the major carbon and energy source. This interaction is one of the foundations of the entire ocean food-web. The carbon fixed by phytoplankton can be redirected to bacteria in two main ways; either (i) bacteria feed on dead phytoplankton cells … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…This was evident from both cell count (Appendix S1: Figure S1b) and chlorophyll a content (Appendix S1: Figure S1c). This stimulating effect, previously reported by Bruckner et al (2011) and Daly et al (2021), is possibly due to the presence of bacterial exudates, which serve as substrates to support P. tricornutum under mixotrophic growth (Villanova & Spetea, 2021). Previous studies revealed that glucose and fructose exerted significant enhancement on the growth of P. tricornutum under mixotrophic conditions (Cerón-García et al, 2013;Villanova et al, 2017).…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…This was evident from both cell count (Appendix S1: Figure S1b) and chlorophyll a content (Appendix S1: Figure S1c). This stimulating effect, previously reported by Bruckner et al (2011) and Daly et al (2021), is possibly due to the presence of bacterial exudates, which serve as substrates to support P. tricornutum under mixotrophic growth (Villanova & Spetea, 2021). Previous studies revealed that glucose and fructose exerted significant enhancement on the growth of P. tricornutum under mixotrophic conditions (Cerón-García et al, 2013;Villanova et al, 2017).…”
mentioning
confidence: 59%
“…The co‐culture of Phaeodactylum tricornutum ‐ Pseudoalteromonas haloplanktis , as well as the bacterial and diatom controls, were set up following the methods described in Daly et al (2021) with some modifications. Briefly, the preculture of Ps.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In a coculture of P. tricornutum and the bacterium Pseudoalteromonas haloplanktis , the exo-environment described by exo-monosaccharide profiles varied depending on the culture condition [ 149 ]. This bacterium can utilize diatom-released compounds [ 150 ]. Algal-derived dissolved organic carbon and nitrogen and bacterial incorporation of these remineralized compounds were studied with P. tricornutum and several different bacteria.…”
Section: Marine Microalgaementioning
confidence: 99%
“…The decomposition and mineralization of dissolved organic materials by heterotrophic bacteria are essential to their survival and proliferation (Falkowski et al, 2008). Due to the limited available nutrients in the culture medium, the phycosphere bacteria primarily interacted with algae in the indoor culture environment, and the usage of organic substances generated by algae was the primary survival method of the bacteria (Daly et al, 2021;Kim et al, 2022). In this experiment, as P. tricornutum entered the exponential growth phase, a large number of metabolites secreted by algae might have increased the bacterial diversity index.…”
Section: Changes In the Bacterial Diversity Index And Communities Und...mentioning
confidence: 99%